Has Anti-Migration and Anti-Refugee Discourse Hampered Progress against Child Labour? - Simon Steyne (Revista Tecnológica)
The chequered application, since 2000, of integrated policies to eradicate the intersectional root causes of child labour sits more recently in a wider political context of recrudescent populist ethnonationalism accompanied by weakened respect by the governments of many countries for the rules-based international system and rights-based development. The author suggests that (apart from Northern-centric trade and policy interests) influential populist-nationalist governments (including those of the United Kingdom (linked to Brexit), and Australia (linked to the “Bali Process”) have contributed to diverting global attention from the largest cohort intended to benefit from Sustainable Development Goal Target 8.7 - the 160 million children now in child labour - by conflating forced labour with trafficking and trafficking with migration and asylum. This conflation seeks to demonise asylum-seekers, refugees, and economic migrants. It is an important element of the discourse of populist-nationalist ruling parties in their search for continued electoral support and reflects a willingness to violate international law protecting human rights.